Burnout syndrome, doctor-patient relationship and family support of pediatric medical staff during a COVID-19 Local outbreak in Shanghai China: A cross-sectional survey study - Lyu, Baiyu; Xu, Meijia; Lu, Lijuan; Zhang, Xiaoying (Frontiers in Pediatrics, 2023)
Objectives To explore burnout syndrome (BOS) incidence, doctor-patient relationship, and family support on pediatric medical staff in Shanghai comprehensive hospitals during a COVID-19 local outbreak. Methods A cross-sectional survey of pediatric medical staff from 7 comprehensive hospitals across Shanghai was conducted from March to July 2022. The survey included BOS, doctor-patient relationships, family support, and the related factors of COVID-19. The T-test, variance, the LSD-t test, Pearson's r correlation coefficient, and multiple regression analyses examined the data. Results Using Maslach Burnout Inventory-General Survey (MBI-GS), 81.67% of pediatric medical staff had moderate BOS, and 13.75% were severe. The difficult doctor-patient relationship was positively correlated with emotional exhaustion(EE), cynicism(Cy), and negatively with personal accomplishment(PA). When medical staff need help, the greater the support provided by the family, the lower the EE and CY, and the higher the PA. Conclusion “In our study, the pediatric medical staff in Shanghai comprehensive hospitals had significant BOS during a COVID-19 local outbreak.” We provided the potential steps that can be taken to reduce the increasing rate of BOS in pandemics. These measures include increased job satisfaction, psychological support, maintaining good health, increased salary, lower intent to leave the profession, regularly carrying out COVID-19 prevention training, improving doctor-patient relations, and strengthening family support.